The Importance of Learning for Changing Sexual Practices in Response to the HIV/AIDS Crisis in Ghana - Augustine M. Amenyah; Bradley C. Courtenay (Adult Education Research Conference, 2006)
This study examined how adults in Ghana learned to make changes in their sexual practices in response to HIV/AIDS crisis. Findings include changes made in sexual practices and a learning process that included four components: initial awareness, catalysts for further learning, engagement in learning activities, and other influential factors.